Large spontaneous median sacral artery pseudoaneurysm masquerading as hip pain - Faraj, Joseph (J Vasc Surg Cases Innov Tech, 2020)
We report the case of an 81-year-old man who presented with severe right hip pain and reduced physical function secondary to a large spontaneous median sacral artery pseudoaneurysm measuring 83.5 × 55.4 mm. The patient had no history of recent trauma, infective or inflammatory disease, or any recent procedures. The patient was taking apixaban for atrial fibrillation. Percutaneous coil embolization was used to occlude the pseudoaneurysm. This case describes a novel disease, spontaneous median sacral artery pseudoaneurysm, presenting with hip pain.